Long-Term Survival After Intravenous Thrombolysis for Ischemic Stroke: A Propensity Score-Matched Cohort With up to 10-Year Follow-Up - Muruet, Walter (Stroke, 2018)
BACKGROUND AND PURPOSE—: Intravenous thrombolysis with alteplase is one of the few approved treatments for acute ischemic stroke; nevertheless, little is known about its long-term effects on survival and recovery because clinical trials follow-up times are limited. METHODS—: Patients registered between January 2005 and December 2015, to the population-based South London Stroke Register of first-ever strokes. Propensity score was used to match thrombolyzed and control cases to a 1:2 ratio by demographical and clinical covariates. The primary outcome was survival up to 10 years using Kaplan–Meier estimates, Cox proportional hazards, and restricted mean survival time. Secondary outcomes included stroke recurrence and functional status (Barthel Index and Frenchay Activities Index scores) at 5 years. RESULTS—: From 2052 ischemic strokes, 246 treated patients were matched to 492 controls. Median follow-up time 5.45 years (interquartile range, 4.56). Survival was higher in the treatment group (median, 5.72 years) compared with control group (4.98 years, stratified log-rank test <0.001). The number needed to treat to prevent 1 death at 5 years was 12 and 20 at 10 years. After Cox regression analysis, thrombolysis reduced risk of mortality by 37% (hazard ratio, 0.63; 95% confidence interval [CI], 0.48–0.82) at 10 years; however, after introducing a multiplicative interaction term into the model, mortality risk reduction was 42% (hazard ratio, 0.58; 95% CI, 0.40–0.82) at 10 years for those arriving within 3 hours to the hospital. On average, in a 10-year period, treated patients lived 1 year longer than controls. At 5 years, thrombolysis was associated with independence (Barthel Index≥90; odds ratio, 3.76; 95% CI, 1.22–13.34) and increased odds of a higher Frenchay Activities Index (proportional odds ratio, 2.37; 95% CI, 1.16–4.91). There was no difference in stroke recurrence. CONCLUSIONS—: Thrombolysis with intravenous alteplase is associated with improved long-term survival and functional status after ischemic stroke.